2022
DOI: 10.1155/2022/3125662
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen-Day Evolution of COVID-19 Symptoms during the Third Wave in Nonvaccinated Subjects and Effects of Hesperidin Therapy: A Randomized, Double-Blinded, Placebo-Controlled Study

Abstract: COVID-19 symptoms can cause substantial disability, yet no therapy can currently reduce their frequency or duration. We conducted a double-blind placebo-controlled trial of hesperidin 1000 mg once daily for 14 days in 216 symptomatic nonvaccinated COVID-19 subjects. Thirteen symptoms were recorded after 3, 7, 10, and 14 days. The primary endpoint was the proportion of subjects with any of four cardinal (group A) symptoms: fever, cough, shortness of breath, or anosmia. At the baseline, symptoms in decreasing fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…An in-vitro study found that the drug molecule 'simeprevir' significantly decreases the SARS-CoV-2 viral load 152 . In a double-blind placebo-controlled trial, the drug 'Hesperidin 1000 mg daily may help decrease fever, cough, shortness of breath, or anosmia symptoms of nonvaccinated COVID-19 infected patients 169 . In histopathological, biochemical, and micro-CT analyses on rat, Hesperidin successfully reduced the severity of lung injury caused by BLC, a model for IPF 168 .…”
Section: Discussionmentioning
confidence: 99%
“…An in-vitro study found that the drug molecule 'simeprevir' significantly decreases the SARS-CoV-2 viral load 152 . In a double-blind placebo-controlled trial, the drug 'Hesperidin 1000 mg daily may help decrease fever, cough, shortness of breath, or anosmia symptoms of nonvaccinated COVID-19 infected patients 169 . In histopathological, biochemical, and micro-CT analyses on rat, Hesperidin successfully reduced the severity of lung injury caused by BLC, a model for IPF 168 .…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted by Dupuis et al [ 36 ] presented the findings of a randomized, double-blinded, placebo-controlled study conducted to investigate the evolution of COVID-19 symptoms over a 14-day period in nonvaccinated COVID-19 individuals. The intervention involved administering hesperidin at 1000 mg once daily for 14 days, while the control group received a matching placebo.…”
Section: Hesperidin Versus Sars-cov-2mentioning
confidence: 99%
“…Hesperidin also blocks the AKT pathway and inhibits Ang II-induced collagen expression and cardiac fibroblast proliferation during COVID-19 infection [ 121 ]. Clinical studies have also shown that hesperidin can reduce some of the clinical symptoms of COVID-19, such as shortness of breath, cough, decreased or even absent taste, and fever [ 122 ].…”
Section: Anti-sars-cov-2 Activity Of Flavonoidsmentioning
confidence: 99%